PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN ISLAMIC ADVERTISING TERHADAP REPUTASI PERUSAHAAN DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PENGGUNA LAPTOP ASUS DI KOTA SALATIGA - Santika, Selvia Ayu; Kurniawan, Heri (Faculty of Economics and Business University of Lampung, 2023)
The study aims to identify and analyze the impact of corporate social advertising and Islamic advertising on the company's reputation, with customer satisfaction as a variable of intervening on ASUS laptop users in Salatiga City. This quantitative research uses questionnaires as a preliminary data source. The IBM SPSS 25 statistical analysis tool is used to analyze a sample of 100 respondents. The results of this study indicate that the implementation of corporate social responsibility, Islamic advertising, and customer satisfaction each has a positive and significant effect on company reputation. Corporate social responsibility has a positive and significant effect on customer satisfaction. Islamic advertising has a positive and insignificant effect on customer satisfaction. The customer satisfaction variable can mediate corporate social responsibility's influence on a company's reputation. Meanwhile, customer satisfaction cannot mediate Islamic advertising on a company's reputation. Keywords: Customer Satisfaction, Corporate Social Responsibility, Islamic Advertising, Company Reputation.